Chronic pelvic pain in women: an embedded qualitative study to evaluate the perceived benefits of the meridian balance method electro-acupuncture treatment, health consultation and National Health Service standard care. Issue 4 (November 2019) - Chong, Ooi Thye; Critchley, Hilary OD; Horne, Andrew W; Fallon, Marie; Haraldsdottir, Erna
Introduction: Chronic pelvic pain (CPP) – defined as intermittent or constant pain in the lower abdomen or pelvis of at least 6 months' duration, not occurring exclusively with menstruation or intercourse and not associated with pregnancy – is estimated to affect 6–27% of women worldwide. In the United Kingdom, over 1 million women suffer from CPP, which has been highlighted as a key area of unmet need. Current medical treatments for CPP are often associated with unacceptable side effects. A specific style of acupuncture, the meridian balance method electro-acupuncture (BMEA) and traditional Chinese medicine health consultation (TCM HC (BMEA + TCM HC = BMEA treatment)), may be effective for CPP in women. Aim: Three focus group discussions and semi-structured telephone interviews were embedded in a randomised controlled feasibility trial to gain in-depth description of the perceived benefits of the participants' respective interventions. Methods: Women with CPP were randomised into the BMEA treatment, TCM HC or National Health Service standard care (NHS SC). Focus group discussions were recorded, transcribed and analysed thematically. Semi-structured telephone interviews were conducted post focus group discussions. Findings: A total of 30 women were randomised into BMEA treatment, TCM HC or NHS SC. A total of 11 participants attended the three focus group discussions. Thematic analysis of focus group discussions showed: a perceived pain reduction, enhanced sleep, energy level and sense of well-being in the BMEA treatment and TCM HC groups; a dislike for the adverse effects of medications, frustration at the lack of effective treatment, heavy reliance on medications and services that are helpful, in the NHS SC group. Semi-structured telephone interviews showed that the methodology was acceptable to the participants. Conclusion: The embedded focus group discussions captured the rich and complex narratives of the participants and provided insights into the perceived benefits of the BMEA treatment, TCM HC and NHS SC interventions.